KINERJA PELAYANAN APARATUR DALAM SERTIFIKASI TENAGA PENDIDIK DI DINAS PENDIDIKAN KABUPATEN HULU SUNGAI UTARA - M. Husaini M. Husaini (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
The objective of this research is to know service performance of the apparatus in the certification of educators in the Education Office of Kabupaten Hulu Sungai Utara and factors affecting the service performance of the apparatus are in the certification of educators in the Education Office of Kabupaten Hulu Sungai Utara. The research method used is a qualitative research method using a descriptive analysis technique, with techniques of documentation and interviews. The informants in obtaining the data are the Head of the Office, Secretary, Chief of Department. Chiefs of Sections, Head of Sub-sections and also the staff at the Education Office of Hulu Sungai Utara.The result showed that the service performance of the apparatus in the certification of educators in the Education Office of Hulu Sungai Utara has not been optimal yet when seen from the actual tasks and functions. Factors affecting are professionalism factor and organizational structure of the financial managers of educators certification in the Education Office of Hulu Sungai Utara. It can be seen from the aspect of the distribution of tasks which is unclear and is still overlapped in the work, as well as other aspects that the authorities have not been fully delegated for employees in accordance with the existing position and title.